ANALISIS LINGKUNGAN INTERNAL - EKSTERNAL PADA PASAR RAKYAT KERTHA, DESA KESIMAN KERTALANGU - Ida Ayu Made Dwi Susanti; I Made Budiasa; Cokorda Javandira (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2019)
Globalization shows us that many of the changes that occur in a variety of ways, including a market. This role is an important consequence of the changing patterns of consumption and culture in everyday at the world comunity, including Indonesia. The results showed that the main strengths factor in the internal accessibility and the main weaknesses are the quality of human resources (merchants). External factors that are major are opportunities tourist arrivals and the main factors that threaten the stability of product prices in the modern market